PEMBUATAN KURVA ISODOSIS PAPARAN RADIASI DI RUANG PEMERIKSAAN INSTALASI RADIOLOGI RSUD KABUPATEN KOLAKA - SULAWESI TENGGARA - Syahria, Syahria; Setiawati, Evi; Firdausi, K Sofjan (BERKALA FISIKA, 2012)
t have been conducted research about the influence of distance variability betweensecondary radiation source and the determining spot to scatter radiation exposure in theinspection room I radiology instalation RSUD Kolaka – South East Sulawes, it producted isodosecurve .This research use phantom, in the form of water in the plastic container high 40 cm andwidth 21 cm, with exposure wide 30× 40 cm. Exposure condition is given by fixed expose factor covering of tube voltage 90 kV, tube current 150 mA and exposure time 0.8 second. Sample in this research is distance of 1 meter; 1,5 meter and 2 meter from the secondary radiation source to thedetermining spot, which measuring the scatter radiation exposure is directly conducted by thesurvey meter measuring instrument.The result of research indicates that the amount of thescattered radiation exposure will downhill progresivley to addition distance, so it can know thepoints/places that safe to the scatter radiation exposure. It can also know the maximum time limitallowed for a radiator worker in the inspection room I.Keywords : Isodose Curve , Phantom, Expose factor, Scatter radiation exposure.